The Influence of the Brand on the Purchasing Behavior of Agricultural Machinery - Aurelian-Cosmin Balan (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
The influence of the brand in the purchasing process of agricultural machinery plays an essential role in the decisions made by farmers and agricultural companies. In an increasingly competitive market, established brands stand out through their reputation, technological innovation, product quality, and the loyalty relationships they build with their customers. The selection of agricultural machinery is based not only on technical features or price but also on the perception that farmers have of the brand, as well as on previous experiences and the support offered post-sale. Factors such as equipment reliability, brand recognition, availability of spare parts, and maintenance services contribute to making an informed purchasing decision. Evaluating the brand's influence on agricultural machinery purchases includes indicators such as customer satisfaction, long-term performance, and technological innovation. These elements are complementary in analyzing brand competitiveness in this sector and represent key factors in determining the choices made by farmers. At the same time, the brand's influence is measured by its ability to provide sustainable solutions that combine operational efficiency with environmental care. Strategies proposed to increase a brand's influence in the agricultural machinery market focus on innovation, quality technical support, and lasting customer relationships, all contributing to creating a long-term competitive advantage.